Multi-Goal Programming Model for Optimal Priority in Building Material Production Planning - Hendra Cipta; Rina Widyasari (Jurnal Matematika UNAND, 2026)
One crucial activity for a company’s long-term sustainability is establishing an effective production planning policy. Currently, CV Lembah Melintang relies on consumer demand to determine its production process, which often leads to suboptimal resource utilization. This research aims to develop an optimal production plan using a Multi-Goal Programming (MGP) model to maximize resource use and increase company income. The MGP model, an extension of the goal programming method, allows for multiple objectives by incorporating deviation variables to handle conflicts between goals. In this study, the objectives are: maximizing total production, minimizing production costs, and maximizing profit, subject to relevant resource constraints. Data analysis and computation were carried out using POM-QM v5 software. The results indicate that the production plan successfully met the company’s targets: sales volume was achieved, production costs remained below the target limit of IDR 922,105,662.4, and profit reached the target of IDR 564,080,764 for the 2023 period. The study concludes that the MGP model is an effective decision-support tool for improving production planning policies and aligning multiple strategic goals in manufacturing environments.